Quality of life vs. coping with stress by nurses during the COVID-19 pandemic - Kupcewicz, Ewa; Piwko, Grażyna; Araminowicz-Kierklo, Elżbieta; Młynarska-Antochów, Katarzyna (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic, one of the greatest global health challenges of the 21st century, had a significant impact on the quality of life of healthcare personnel. It is par-ticularly nurses who, as front-line workers in the fight against the pandemic, have experi-enced a deterioration in their physical and psychosocial health. The increased workload, fear of infection, and stress associated with the epidemic situation had a significant impact on their well-being and quality of life.Aim of the studyTo understand how nurses perceived their quality of life during the COVID-19 pandemic and to determine the role of stress-coping strategies in relation to the consequences of the spread of SARS-CoV-2 virus infections.Materials and methodsThe study employed the diagnostic survey method with a group of 202 nurses working in hospitals in the city of Ełk between March and May 2021. The empir-ical data were collected using the WHOQoL-Bref Quality of Life Questionnaire, the Mini-COPE inventory, and a questionnaire developed by the authors of the study.ResultsSignificant correlations were observed between six stress-coping strategies and the psychological domain of the nurses’ quality of life. These include: “Active coping” (r = 0.242; p < 0.001), “Positive revalidation” (r = 0.153; p < 0.03), “Self-blaming” (r = −0.152; p < 0.03) and “Seeking instrumental support” (r = 0.227; p < 0.001). Analysis of predictors of quality of life showed that three stress-coping strategy groups, i.e., “A sense of humour,” “Helplessness” and “Seeking support,” achieved the R2 value in the regression model falling within the range of 0.02–0.08.ConclusionChoosing appropriate stress-coping strategies can be an important factor in determining the nurses’ quality of life during crises such as a pandemic.